2016
DOI: 10.1098/rspb.2015.2572
|View full text |Cite
|
Sign up to set email alerts
|

Fitness costs of worker specialization for ant societies

Abstract: Division of labour is of fundamental importance for the success of societies, yet little is known about how individual specialization affects the fitness of the group as a whole. While specialized workers may be more efficient in the tasks they perform than generalists, they may also lack the flexibility to respond to rapid shifts in task needs. Such rigidity could impose fitness costs when societies face dynamic and unpredictable events, such as an attack by socially parasitic slavemakers. Here, we experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…longispinosus (Jongepier & Foitzik, 2016). Moreover, we recently showed that a decrease in worker size variation did not affect the efficiency of various colony level tasks in T. nylanderi (Colin T., Doums C., Péronnet R., Molet M., unpublished data).…”
Section: Introductionmentioning
confidence: 83%
“…longispinosus (Jongepier & Foitzik, 2016). Moreover, we recently showed that a decrease in worker size variation did not affect the efficiency of various colony level tasks in T. nylanderi (Colin T., Doums C., Péronnet R., Molet M., unpublished data).…”
Section: Introductionmentioning
confidence: 83%
“…This highlights an interesting contradiction; it suggests that although some workers are highly active and conform to the definition of 'elites', they may not actually be that effective at their task, despite investing more effort than their nest mates. Indeed, a recent study, also in the Temnothorax genus, found that reliance on specialists in the face of dynamic environments may be disadvantageous (Jongepier and Foitzik, 2016), highlighting another case in which the contribution of 'elites' is far from decisive.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, some T. longispinosus workers fight against their slavemaker attackers, while others start to evacuate the nest and flee with the brood [120]. However, division of labour can also be maladaptive when facing slavemakers [121]: manipulation of the level of division of labour in T. longispinosus hosts showed that colonies composed of generalist workers saved more brood and inflicted more casualties among their slavemaker attackers than colonies composed of specialist workers. Moreover, comparing the natural level of division of labour in host colonies across populations confirmed that hosts were less specialized when threatened by slavemakers.…”
Section: (B) Larger Fightersmentioning
confidence: 99%